2016
DOI: 10.3758/s13423-016-1048-z
|View full text |Cite
|
Sign up to set email alerts
|

The Face-Race Lightness Illusion Is Not Driven by Low-level Stimulus Properties: An Empirical Reply to Firestone and Scholl (2014)

Abstract: Levin and Banaji (Journal of Experimental Psychology: General, 135, 501-512, 2006) reported a lightness illusion in which participants appeared to perceive Black faces to be darker than White faces, even though the faces were matched for overall brightness and contrast. Recently, this finding was challenged by Firestone and Scholl (Psychonomic Bulletin and Review, 2014), who argued that the nominal illusion remained even when the faces were blurred so as to make their race undetectable, and concluded that un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 10 publications
0
13
0
Order By: Relevance
“…Firestone and Scholl [ 27 , 28 ] introduced this account, as a case study within a more general discussion about “cognitive penetrability” in perception or top-down cognitive biases. By showing degraded (blurred) versions of the original images, they found that participants continued to yield the same bias, despite being unable to categorize the stimuli as either ethnicity (but see [ 29 ] for a rebuttal). Most interestingly, Firestone and Scholl hinted at the possibility that spontaneous patterns of eye movements on such salient features could be at the basis of the response bias and explicitly stated that a face could look darker if gaze or attention was captured by its salient dark parts.…”
Section: Introductionmentioning
confidence: 99%
“…Firestone and Scholl [ 27 , 28 ] introduced this account, as a case study within a more general discussion about “cognitive penetrability” in perception or top-down cognitive biases. By showing degraded (blurred) versions of the original images, they found that participants continued to yield the same bias, despite being unable to categorize the stimuli as either ethnicity (but see [ 29 ] for a rebuttal). Most interestingly, Firestone and Scholl hinted at the possibility that spontaneous patterns of eye movements on such salient features could be at the basis of the response bias and explicitly stated that a face could look darker if gaze or attention was captured by its salient dark parts.…”
Section: Introductionmentioning
confidence: 99%
“…While we do not wish to engage in a discussion about whether such an interaction between race assumptions (in terms of the expected surface reflectance patterns) and traditional mechanisms for reflectance computations would constitute a ‘top-down’ contextual influence, we note that such an interaction would be congruent with Baker and Levin [32]’s observations that lightness judgments relate well to observers’ assignments of race categories. Critically, however, if we draw upon speculations underlying other-race effects in the traditional face literature, that is, that such effects manifest in better efficiencies in encoding own-race category faces [40,44,45,46]—then it follows that we should have observed additional expertise-dependent modulations in lightness judgments should the two phenomena be related.…”
Section: Discussionmentioning
confidence: 69%
“…While our procedures of luminance and contrast normalization should have acted to reduce the saliency of these differences somewhat, they are nevertheless still retained to some degree. Still, we note that in their reply to Firestone and Scholl [31], Baker and Levin [32] used photonegative (luminance-inverted) versions of blurred stimuli (which preserved such spatial heterogeneities across races, albeit inverted), and found that observers no longer judged one face to be lighter than the other (which was the case of judgments for the veridically blurred stimuli). Thus, it seems unlikely that low-level differences alone, and specifically with respect to differences in spatial distribution, could explain the data observed here (and elsewhere; [25,32]).…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations